Lesson [thinking light bulb represent I]deas for communicative English - Marina Abu Bakar; Yang, Wan Ling; Yeo, Li Min (Oxford Fajar Sdn. Bhd., 2015)
This book is written with the aim of sharing tested materials with English language educators. Specially designed with tertiary students in mind, this book covers the objectives and encompasses the four language skills-namely reading, speaking, listening and writing-in various activities. Educators will find the student-centred activities featured in this book useful. In line with an outcome-based education, these activities are geared towards motivating and aiding students of different learning styles and abilities in learning the English language. It is hoped that this book will help to lighten the burden of educators, in terms of time needed to conceive ideas for classroom activities. Besides that, it is hoped that the materials in this book will help to illustrate that pedagogical strategies can easily be adapted and used for different topics.